(untitled) (LACCEI, 2024)
The objective of this research is to validate the thermal amplitude model of Bristow - Campbell to estimate the solar resource in the development of clean energy in the city of Huancayo (Junín - Peru) during the period 2020. The results obtained from the model were compared with the values obtained with the use of the pyranometer as a meteorological instrument, using temperature data. To estimate the available radiation throughout 2020, 732 data of maximum and minimum temperatures were downloaded obtaining 2 data/day for 366 days from the conventional meteorological station of SENAMHI installed in the province of Huancayo and for the validation process, 366 global data of solar radiation data measured by the pyranometer equipment on surface were used, the same that were downloaded from the Observatory of the Geophysical Institute of Peru (IGP) of Huancayo, the results of solar radiation estimated with the model presented an annual average of 6. 14kWh/m2/day and with the pyranometer a value of 5.76 kWh/m2/day, the regression analysis between the estimated and measured data shows a value of r equal to 0.90, with the variation of the estimated radiation of 6.15 ± 0.36 and the measured radiation of 5.76 ± 1.24 kWh/m2/day Thus, the use of the Bristow and Campbell model to estimate the global radiation in the province of Huancayo was presented as an adequate and efficient alternative.